6 Transistors and 1 memristor based memory cell - Kazi Fatima Sharif; Satyendra N. Biswas (Institute of Advanced Engineering and Science, 2020)
Area efficient and stable memory design is one of the most important tasks in designing system on chip. This research concentrates in designing a new type of hybrid memory model by using only nMOS transistors and memristor. The proposed memory cell is very stable during successive read operates and comparatively faster and also occupies less amount of silicon area. The stability of the data during successive read operation and noise margin are in the promising range. Extensive simulation results using LTspice and Cadence software tools demonstrate the validity and competency of the proposed model.